EFFICIENCY OF TWO MOLECULAR TOOLS BASED ON DNA USED FOR DIFFERENTIATING SOME MICROBIAL STRAINS - Samar El-Masry; M. Sadik; B. Akl (Arab Universities Journal of Agricultural Sciences, 2019)
In the present study, two molecular biology tools based on DNA were compared in the differentiating between some microbial strains isolated from soil. Two types (16SrRNA and 18SrRNA) of ribosomal RNA genes were used for identification of the four bacterial and three fungal isolates, respectively. The identified microbial isolates were submitted in GenBank as strains of Escherichia coli MSL-19 (LC455952.1); Bacillus sp. MSLB-1 (LC455953.1); Bacillus sp. MSLB2 (LC455954.1); Bacillus sp. MSLB3 (LC455955.1); Penicillium sp. MLSP1 (LC455956.1); Aspergillus niger MLSAs1 (LC455958.1); Aspergillus sp. MLSAs2 (LC455959.1). The DNA obtained from the seven microbial strains was used as templates for RAPDPCR differentiating in the presence of eight random primers. Electrophoresis analysis was performed, and on scoring, the identity percentages between the bacterial and fungal strains were separately analyzed. A percentage of 82-83% was recorded between the E. coli and the three Bacillus strains, while, identities of 93-98% were recorded between the three Bacillus strains. Similar trend (90-96%) was observed between the Penicillium and Aspergillus strains. Results confirmed that identities based on the two ribosomal RNA genes (82-98%) was higher than that of RAPD-PCR (70.0-79.7%), and this is because of ribosomal RNA genes are in limited sizes (~1500-1600 bp) and specific for differentiating species, while RAPD-PCR tool depends on using some random primers could be recorded on the whole genome. The phylogenetic trees based on the two molecular  tools supported the obtained results. As a conclusion, tools of RAPD-PCR and ribosomal RNA genes were successfully used to identify and detect the genetic variability of microbial strains isolated from soil.